Strategi Pengembangan Usaha Wisata Homestay Berbasis Komunitas di Kabupaten Raja Ampat, Provinsi Papua Barat - Selna Adesetiani; M Kolopaking, Lala; Eriyatno, Eriyatno (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2021)
Raja Ampat is one of the regencies in Papua that has accelerated the development of tourism activities due to its biodiversity. The tourism potential of Raja Ampat impacts the transformation of social change from fishing tribes to sustainable ecotourism management communities. This study aims to analyze: 1) potentials, constraints, and needs for developing a community-based Homestay business of the indigenous people of Raja Ampat; 2) outsiders’ intervention as well as financial access; 3) and the direction of community business development for homestay owners in Kampung Yenbuba and Kampung Arborek, Raja Ampat. The approach used in this study is a qualitative approach with a constructivism paradigm. The data collection techniques were done by applying the methods of observations, interviews, documentation, focus group discussions, and secondary data collections. The result showed that by managing a Homestay business in Raja Ampat, there was a significant increase in terms of the economy compared to when people worked as fishermen. The intervention from various parties such as the government, Non-Governmental Organizations, and the private sectors are very influential in implementing community-based tourism business development. Thus, there is a need for development directions in gaining access to various available resources and the participation of external parties to increase human resource capacity, access to finance, connectivity, and digitalization.